Effect of compressed natural gas on performance and emission of a 4-stroke spark ignition engine - Awang, Idris (2009)
This thesis deals with experimental study of a four-stroke spark ignition engine. The objective of this thesis is to evaluate the performance and emission characteristics of the engine while using conventional fuel, gasoline and alternative fuel, compressed natural gas (CNG). The engine operated under a steady state condition at wide-open throttle condition. The performance and emissions test was performed with various constant loads at different speed within the range of 1500 rpm to 4000 rpm with 500 rpm interval. The first experiment is executed by using gasoline and followed by CNG. The engine performance and emissions such as air-fuel ratio, torque, brake power, brake specific fuel consumption, efficiency, the concentration of CO, CO2, HC, and NOx of gasoline and CNG were measured. The results demonstrated that the potential of reducing emissions while applying CNG as fuel is obvious. However the performance of CNG is reduced as the brake power of engine decrease around 25% compare to gasoline engine. During operate with CNG the engine emissions of CO, CO2 and HC shows a significant reduction but the NOx emission is highly increased compare to gasoline. The results and analysis will be useful for the development of dedicated gas engine in the near future.